On the Association between Perceived Overqualification and Adaptive Behavior - Wu, C.-H.; Tian, Amy; Luksyte, A.; Spitzmueller, C. (Emerald, 2016)
Purpose: The purpose of this paper is to offer an autonomous motivation perspective to explore the relationship between perceived overqualification and adaptive work behavior and examine job autonomy as a factor that may moderate the association. Design/methodology/approach: The hypotheses were tested in two culturally, demographically, and functionally diverse samples: sample 1 was based on North American community college employees (n=215); sample 2 was based on full-time workers, employed in a Chinese state-owned enterprise specializing in shipping (n=148). Findings: In study 1, perceived overqualification was negatively related to self-rated adaptive behavior. A follow-up study 2 extended these findings by demonstrating that perceived overqualification was negatively related to supervisor-rated adaptive work behavior when job autonomy was low, rather than high. Research limitations/implications: The results of this research offer an autonomous motivation perspective to explain why perceived overqualification relates to adaptive behavior and suggests a job design approach to encourage adaptive behaviors of people who feel overqualified – a sizable segment of the current workforce. Originality/value: This is one of the first studies to explore adaptive behavior of workers who feel overqualified – an outcome that has not been examined in this domain. The findings further point out what can be done to encourage adaptive behaviors among overqualified employees.